2003
DOI: 10.1159/000069481
|View full text |Cite
|
Sign up to set email alerts
|

The Grade of Acute Thymus Involution in Neonates Correlates with the Duration of Acute Illness and with the Percentage of Lymphocytes in Peripheral Blood Smear

Abstract: In various stressful conditions, the thymus is subjected to incidental involution, mostly due to the thymocytolytic effect of secreted glucocorticosteroids. The aim of this study was to examine acute thymic involution in sick neonates and to compare the morphological grade with some clinical and laboratorial parameters. The influence of the illness on thymus tissue was investigated in 100 neonates who were treated and died in a neonatology intensive care unit. The preterm infants (n = 73) were born before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…Some of the support for an association between inflammation and acute thymus involution comes from observational studies of human newborns [10,11,21] . In our sample, the inflammation marker that best discriminates between early and late/no thymus involution was fetal vasculitis/funisitis.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the support for an association between inflammation and acute thymus involution comes from observational studies of human newborns [10,11,21] . In our sample, the inflammation marker that best discriminates between early and late/no thymus involution was fetal vasculitis/funisitis.…”
Section: Discussionmentioning
confidence: 99%
“…33 An involution of the fetal/neonatal thymus has also been observed, 34 even in cases of subclinical CA. 35 The grade of thymic involution may be proportional to the duration of the inflammatory process, 36 and it has been associated with lesions of the brain white matter. 37 In addition, the bacterial products and the inflammatory mediators released during FIRS might induce myocardial depression in the fetus.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Low number of lymphocytes in peripheral blood may indicate the involution of thymus in newborns with an acute disease 35 . However, Van Baarlen et al 36 have found neither a correlation between thymus size and the number of lymphocytes nor a correlation between thymus size and the size of other lymphatic organs in healthy children.…”
Section: Cd8mentioning
confidence: 99%